PATTERN OF CORONARY ARTERY DISEASE WITH NO RISK FACTORS UNDER AGE 35 YEARS - Noor, Lubna; Shah, S Sadiq; Adnan, Yasir; Sawar, Shah; Din, Shahab ud; Amina, Amina; Awan, Zahid Aslam; Bangash, Kamran; Ahmed, Saeed; Dad, Aqal (Journal of Ayub Medical College Abbottabad, 2010)
Background: Coronary artery disease (CAD) is no more deemed to be an ailment of the 4th or 5th decade; rather an earlier age incidence is not infrequently encountered in our population. However, there are a few data regarding CAD in young adults, and much about its underlying pathology still remains undetermined. The objective of this study was to delineate the coronary arterial disease pattern in adults under the age of 35 years, but having no known coronary risk factors. Methods: This prospective study was conducted at the Cardiology Departments of all 3 public sector tertiary care hospitals in Peshawar from Jun 2008 to Dec 2009. After having excluded the traditional risk factors for CAD, patients under the age of 35 years with objective evidence of CAD were subjected to percutaneous coronary angiography. Results: Out of a total of 104 patients, 85 (81.73%) patients were men, and 19 (18.27%) were women. The mean age of the whole group was 32.66±3.237 (22-35) years. Significant CAD (>50% diameter narrowing of at least one major coronary artery) was found in 87 (83.7%) patients while 17 (16.3%) patients had non-atherosclerotic coronary artery disease, including 12 (11.53%) patients having normal coronary arteries, 1 (1%) patient had anomalous origin of right coronary artery (RCA), 1 (1%) patient had coronary arteritis, 2 (1.92%) patients had coronary artery ectasia, and 1 (1%) patient had a myocardial bridge over left anterior descending artery (LAD). Among the patients with significant CAD, the prevalence rate of one, two and three vessel disease was 54 (51.9%), 22 (21.2%) and 11 (10.6%) respectively. Almost 50% of the lesions occurred in LAD followed by 25% in RCA and 20% in circumflex, while only one patient (1%) had isolated significant CAD of left main coronary artery. Osteal segments were involved in 10%, proximal in 61%, mid in 21% and distal segments in 7% of the lesions. Conclusion: In the younger age group, CAD is mostly a disease of men, single vessel CAD predominates with LAD involvement mostly, predominant osteal to proximal segment involvement of vessels, and a much higher incidence of normal coronaries and non-obstructive CAD is met with. Keywords: Coronary Artery Disease (CAD), Myocardial infarction (MI), Coronary Angiography, Risk Factors